(untitled) (The Himalayan Geographers, 2023)
Tourism is a profound source of foreign earnings all over the world and supports the sustainable management of protected areas as a market-driven solution catering to the increasing number of discriminating travellers seeking to explore and enjoy the natural environment. The financial sustainability of the protected areas is critical for improving their effectiveness in conserving biodiversity. Contingent valuation surveys were administered to 300 non-South Asian foreign visitors (NSAF), South Asian foreign visitors (SAF) and domestic visitors to the Annapurna Conservation Area, during October and November of 2019. The logit regression results suggested that bid amount, income, visitor satisfaction, membership of an environmental organization, education and the environmental concern score are the major determinants affecting the willingness to pay (WTP). The mean willingness to pay for the entrance fee at Annapurna Conservation Area was found to be US 28.23 for NSAF, and US 18.25 for SAF which aren’t significantly more than the present entry charges for Annapurna Conservation Area (ACA). Through this research, it is suggested that the present entry costs remain the same, suggesting that other mountain-protected areas in Nepal should also continue to charge the same amount as the entry fee.